School management team members' perceptions of their roles in managing Grahamstown secondary schools - Tyala, Zakunzima (Rhodes University, Faculty of Education, Department of Education, 2005)
During the apartheid era, that is, before 1994, the education management system in South Africa was fragmented, authoritarian and top-down. Principals were expected to manage schools on their own without consulting the rest of the staff. The birth of political democracy in 1994 resulted in many changes in the education system. These changes include the creation of one national department. In line with this democratisation came the concept of school management teams (SMTs). Because of the democratic nature of this kind of a structure (SMT), it is required that educators work co-operatively and as a team. This has been problematic in some schools where the principal has traditionally felt comfortable taking decisions on his or her own without any input from relevant stakeholders. Furthermore, through the legacy of apartheid, teachers themselves have dogmatically been oriented to being the recipients of instructions and to view management as the prerogative of the principals only. The formalisation of SMTs thus brings new challenges to both principals and staff members, essentially the notion of democratic or team-management. The object of this study is to find out how the concept of democratic management is being received. This study includes all the government-aided high schools in Grahamstown (ten of them). Studying all 10 high schools - 6 from the local township, 3 ex-model C schools, and 1 from the coloured township "“ has produced a broad and varied picture of how SMTs are being received in Grahamstown secondary schools. The study was framed within the interpretive approach, and sought to unpack the perceptions of SMT members with regard to SMTs. An interpretive paradigm made it possible for me to gain an in-depth understanding of SMT members' perceptions of team-management within their contexts. I used questionnaires, interviews and observation as research tools to gather data. This study has found that, although the concept of team management is well-received, there are significant obstacles to the acceptance of teamwork as an alternative form of management. Many of these may be the result of decades of disempowering governance strategies, resulting in impoverished notions of school ownership and joint responsibility. Some relate to the political nature of schools as organisations. Despite these problems, the study has confirmed that team-management is the preferred approach for a variety of reasons. Team-management usually results in enriched decision-making, the sharing of responsibilities and higher levels of support. A major systemic shortcoming highlighted by the study is the absence of meaningful training in democratic educational management.
Keywords: School management teams -- South Africa -- Grahamstown; School management and organization -- South Africa -- Grahamstown; Educational leadership -- South Africa -- Grahamstown; Education, Secondary -- South Africa -- Grahamstown